Academic Dads Balance from the Sidelines: Waiting to Get in the Game. - Vancour, Michele L. (2009)
Keywords: dept.pch; faculty_collection; sabbatical_report

Online research to guide knowledge management planning - Steckler, A.; Farel, A.; Bontempi, J.B.; Umble, K.; Polhamus, B.; Trester, A. (Health Education Research, 2001)
The current paper describes the process and results of an effort to find a way to effectively manage and diffuse prevention knowledge. This study shows the role that today's communication technologies can play in ensuring collaboration and participation in both the design and use of a knowledge management system (KMS) for prevention research, practice and policy. In the context of this study, 'prevention research' includes primary through tertiary prevention efforts consistent with general applied public health research in the US. An online Delphi study was used to engage a set of prevention research constituencies in the design of a mechanism to enhance the potential for effective technology transfer. A three-round Delphi was conducted with 58 stakeholders and key informants involved in prevention: government-level policy makers, researchers and front-line practitioners. The study resulted in consensus on 34 functions and 32 output/content elements of a proposed web-based KMS called Prevention-Effects.net. The paper also describes the implications of both the processes of development and the benefits of the proposed system for those interested in prevention.
Keywords: Delphi Technique; Health Services Research; Humans; Information Services; Internet; Online Systems; Planning Techniques; Preventive Health Services; Technology Transfer; United States; User-Computer Interface; adult; article; dept.pch; health care planning; health care policy; health care system; human; interpersonal communication; major clinical study; management; medical research; priority journal; scoring system

Assisted reproductive technology: Ethical challenges for business and medicine - Flynn, D. (International Journal of Interdisciplinary Social Sciences, 2009)
Assisted Reproductive Technology (ART) is a modern technological tool that provides otherwise infertile individuals and couples an opportunity to conceive. As a multimillion dollar business, ART faces challenges common to other highly profitable enterprises, such as how and when to measure success. This poses ethical challenges as well, though these are unlike the ethical challenges faced by businesses which trade in consumer goods. ART makes babies. Individuals and couples seeking ART may be both vulnerable and fragile, thus ART providers must gently balance smart business practices with ethical care delivery. Applying Laura Nash's integrated approach to business ethics may offer ART providers a suitable model that combines ethically sound care with economically sound business practice. Key to Nash's approach are value creation, economic and social benefit, and relationship building. Not a short-term approach to quick business decisions, Nash's approach requires a long-term commitment as a way of doing business. © Common Ground, Deborah Flynn, All Rights Reserved.
Keywords: Assisted Reproductive Technology; Business Ethics; Infertility; Laura Nash; dept.pch

HIV medication adherence programs: the importance of social support. - Bontempi, Jean M Breny; Burleson, Laura; Lopez, Melissa Hofilena (Journal of community health nursing, 2004)
Since the advent of medical treatments for HIV, the promotion of adherence to these difficult treatment regimens has proven critical to disease management. Three Connecticut state-funded HIV medication adherence programs were evaluated.1 The purpose of this process evaluation was to explore and compare the goals and modality of each adherence program, assess client and staff satisfaction, and provide recommendations for the improvement of these programs. Focus group interviews with clients and individual interviews with staff were conducted at each of the programs. Interviews were transcribed, coded and analyzed with a code and retrieve method of theme identification. Focus group themes included the importance of social support on medication adherence and the "lifesaving" effect the program has had. The staff expressed that although complete adherence should be the long-term objective, more intermediate objectives should be considered (e.g., behavioral changes to increase clients' ability, self-esteem, and self-efficacy to take medications).
Keywords: *Anti-HIV Agents/tu [Therapeutic Use]; *HIV Infections; *Health Promotion/og [Organization & Administration]; *Patient Compliance/px [Psychology]; *Social Support; Anti-HIV Agents; Attitude of Health Personnel; CD4 antigen; Connecticut; Female; Focus Groups; HIV Infections; HIV Infections/dt [Drug Therapy]; HIV Infections/px [Psychology]; Health Knowledge, Attitudes, Practice; Health Promotion; Human immunodeficiency virus infection; Humans; Male; Needs Assessment; Nursing Methodology Research; Organizational Objectives; Outcome and Process Assessment (Health Care); Outcome and Process Assessment, Health Care; Patient Compliance; Patient Education; Patient Education as Topic/og [Organization & Administration]; Program Evaluation; Questionnaires; Self Efficacy; Social Support; Surveys and Questionnaires; United States; antiretrovirus agent; article; attitude; behavior therapy; clinical article; controlled study; dept.pch; drug dose regimen; emotion; evaluation; female; health program; health promotion; human; interview; job satisfaction; male; outcomes research; patient compliance; patient education; professional practice; self concept; self esteem; self medication; social support; staff

Concept mapping as a tool to engage a community in health disparity identification. - Risisky, Debra; Hogan, Vijaya K; Kane, Mary; Burt, Beneta; Dove, Cassandra; Payton, Marinelle (Ethnicity & disease, 2008)
Objectives: To engage a community to critically examine local health disparities. Design: Concept mapping is a tool used to rapidly assess the variations in thinking of large stakeholder groups' about a particular topic. Setting: Jackson, Mississippi. Participants: Community members. Methods: Dialog groups and community meetings were held, and participants were asked to respond to the statement, "A specific thing that causes African Americans to get sicker and die sooner is⋯" Aggregate responses were rated for importance and feasibility and then sorted into related groups. Aggregate sorts and ratings were then processed by using multidimensional scaling and hierarchical cluster analysis. Results: There were 132 (unduplicated) reported contributors to health disparities. These responses fell into eight general clusters: economic issues, government, contextual factors, cultural factors, HIV, stress, environment, and motivation. Factors respondents felt were the most important contributors to disparities (economic factors, contextual factors, stress) did not correlate with those that they thought were most likely to be changed in society (contextual factors, government, motivation). Conclusions: Concept mapping provided a mechanism for rapidly documenting community thinking about health disparities. This mechanism stimulated community dialog and was used as a first step toward the long-term goal of creating equal community, academic, and medical partnerships for addressing disparities. The concept mapping process stimulated critical thinking about contributors to health inequities and uncovered contextual factors previously unknown to researchers and public health planners. The process allowed for active engagement and exchange of knowledge between the community and researchers and allowed a mechanism for identifying and rectifying disconnects in knowledge within and between stakeholder groups.
Keywords: *Community Participation; *Concept Formation; *Health Status Disparities; Adult; African American; African Americans; Aged; Community dialog; Concept Formation; Concept mapping; Consumer Participation; Female; Health Status Disparities; Health disparities; Humans; Jackson; Male; Middle Aged; Mississippi; United States; adult; aged; article; cluster analysis; concept formation; concept mapping; consumer; critical thinking; cultural factor; dept.pch; economics; feasibility study; female; goal attainment; government; health care planning; health status; human; male; medical research; middle aged; motivation; professional practice; public health; scale up; stress; ⛔ No DOI found

Using cognitive mapping to explore women caregivers' experiences - Valentino, Carmela Cassisi; Bulmer, Sandra Minor (American Journal of Alzheimers Disease and Other Dementias, 2005)
Women are often faced with the primary role of providing care for individuals with Alzheimer's disease (AD). This study explored women caregiver's perceptions of caregiving through the use of Cognitive Mapping (CM), a qualitative research method. Volunteers were recruited from caregiver support groups to construct maps of their experience of "caregiving for someone with AD." Maps were analyzed for commonly identified concepts and relationships. Twelve participants identified 280 concepts, 206 of which were unduplicated. Concepts were collapsed into 17 categories; the largest concepts being "friends and family," "sad," "frustration," and "time." The maps produced by the sample in this study were unique, providing evidence that the experience of AD caregiving varies significantly among caregivers. CM appears to be effective for identifying caregiver stressors and needed support services.
Keywords: Alzheimer disease; Alzheimer's disease; Caregivers; Cognitive mapping; Experience; Women; adult; article; brain function; caregiver; cognition; cognitive mapping; concept analysis; dept.pch; experience; family; female; friend; frustration; human; human experiment; loneliness; normal human; patient care; qualitative analysis; social support; stress; time

The same but different: clinician-patient communication with gay and lesbian patients - Bonvicini, Kathleen A; Perlin, Michael J (Patient Education and Counseling, 2003)
Surveys estimate that 3-6% of the patients seen by physicians are gay or lesbian. There are unique health risks of gays and lesbians that are important to the clinician in determining an accurate diagnosis, providing patient education, and arriving at an appropriate treatment plan. One of the most significant medical risks of these populations includes avoidance of routine health care and dissatisfaction with healthcare. Many of these healthcare risks are not addressed because of lack of communication based on a number of common assumptions including the assumption that the patient is heterosexual. This article includes a summary of the medical literature through computerized searches to March 2002 in MEDLINE, PsychInfo, HEALTHSTAR, and bibliographies in articles on health care with gay and lesbian patients. The search strategy included health care of gays and lesbians and clinician-patient communication, partner and family issues. Secondly, it will examine common communication barriers and provide strategies for enhancing communication with patients in a gender-neutral, non-judgmental manner including suggestions for enlisting the inclusion of patients' families. (C) 2002 Elsevier Science Ireland Ltd. All rights reserved.
Keywords: Clinician-patient communication; Family; Gay; Healthcare; Lesbian; MEDLINE; clinical practice; dept.pch; doctor patient relation; family; female; health care; health hazard; heterosexuality; homosexuality; human; interpersonal communication; male; patient education; patient satisfaction; priority journal; review; treatment planning

Secret pills: HIV-positive patients' experiences taking antiretroviral therapy in North Carolina - Golin, C.; Isasi, F.; Bontempi, J.B.; Eng, E. (AIDS Education and Prevention, 2002)
Understanding the barriers to antiretroviral adherence is a critical step in improving the effectiveness of HIV treatment and saving lives. We sought to assess, qualitatively, the experiences of HIV-positive persons taking antiretroviral therapy (ART) in North Carolina. Twenty-four people participated in one of six focus groups. A structured interview script included three questions (two open-ended) and eight probes. Each discussion was taped, transcribed, and content-analyzed. Three distinct themes emerged. First, many participants believed that taking ART was lifesaving but missed doses because they feared that taking them in public would reveal their HIV status. Second, as a result, participants often found it difficult to integrate their regimens into the most basic daily activities. Finally, participants stressed the importance of having open, ongoing dialogues about their treatment plans and privacy needs with a wide range of health care workers. Multidimensional, tailored interventions may help persons living with HIV overcome the stigma and other complex barriers they face in taking antiretroviral therapy.
Keywords: Adult; Antiretroviral Therapy, Highly Active; Attitude to Health; Female; Focus Groups; HIV Infections; Human immunodeficiency virus infection; Humans; Male; Middle Aged; North Carolina; Patient Compliance; United States; adult; antiretrovirus agent; article; attitude to health; clinical article; dept.pch; female; health care personnel; highly active antiretroviral therapy; human; information processing; male; middle aged; patient compliance; patient counseling; privacy; psychological aspect; virus infection

Sexual activity, orgasm and tampon use are associated with a decreased risk for endometriosis. - Meaddough, Erika L; Olive, David L; Gallup, Peggy; Perlin, Michael; Kliman, Harvey J (Gynecologic and obstetric investigation, 2002)
OBJECTIVE: The purpose of the study was to determine if sexual behaviors, orgasm, tampon use, and douching during menstruation modify the risk of endometriosis., METHODS: A case-control study was conducted. Subjects (n = 2,012) consisted of members of the Endometriosis Association and friends not affiliated with the organization who completed mailed surveys. Data were analyzed using chi(2), Fisher's exact test, t test, and regression analyses., RESULTS: There was no difference between study groups concerning douching practices. However, cases were less likely than controls to report sometimes or often engaging in sexual behaviors during menstruation (p = 0.002, OR = 1.5), and sexual behaviors during menstruation that included orgasm (p = 0.001, OR = 1.5). Cases were also less likely than controls to report using only tampons (p < 0.0001, OR = 2.6)., CONCLUSION: Sexual activity, orgasm, and tampon use during menstruation may confer protection against endometriosis. Copyright 2002 S. Karger AG, Basel
Keywords: *Endometriosis/et [Etiology]; *Menstrual Hygiene Products/sn [Statistics & Numerical Data]; *Menstruation; *Orgasm; *Sexual Behavior; Adult; Case-Control Studies; Endometriosis; Female; Humans; Irrigation; Menstrual Hygiene Products; Menstruation; Orgasm; Orgasm/ph [Physiology]; Retrospective Studies; Sexual Behavior; Tampons; Therapeutic Irrigation; adult; article; controlled study; data analysis; dept.pch; endometriosis; female; human; hygiene; major clinical study; menstruation; orgasm; priority journal; regression analysis; sexual behavior; tampon

Can health professionals learn qualitative evaluation methods on the World Wide Web? A case example - Steckler, A; Farel, A; Bontempi, JB; Umble, K; Polhamus, B; Trester, A (Health Education Research, 2001)
The Enhancing Data Utilization Skills through Information Technology (EDUSIT) project trained Maternal and Child Health professionals to collect, analyze and interpret data via a year-long web-based course. The overall goal of the project was to strengthen the technology and analytic skills of the public health workforce. This article describes and analyzes a web-based module for training public health professionals to use qualitative research and evaluation methods that was one of six offered within the EDUSIT project. The qualitative module consisted of six units: overview of qualitative methods, planning qualitative studies, conducting field observations, qualitative interviewing, analyzing qualitative data and presenting qualitative findings. Evaluation results found no statistically significant changes in specific knowledge or beliefs about qualitative methods. However, the change in participants' self-efficacy was statistically significant. Participants' self-reports also showed significant changes in perceived skill levels in `collecting qualitative data through an interview' and `analyzing and interpreting qualitative data'. Most participants rated each lesson within the qualitative methods module as valuable, and most found the teaching methods used satisfactory, emphasizing the value of both the didactic teaching and the practical exercises and team project. The most common difficulty reported was finding the time to complete the module requirements while also working full-time. Implications of these findings for web-based teaching of public health professionals are discussed.
Keywords: Adult; Competency-Based Education; Data Collection; Education, Distance; Education, Graduate; Educational Measurement; Evaluation Studies; Health Knowledge, Attitudes, Practice; Health Personnel; Humans; Internet; Job Satisfaction; Middle Aged; Self Efficacy; Southeastern United States; Teaching; adult; article; data analysis; dept.pch; education; health care personnel; human; human experiment; information processing; priority journal; public health; scoring system; self report; statistical analysis; teaching

Occupational segregation on the playing field: The case of major league baseball - Sack, AL; Singh, P; Thiel, R (Journal of Sport Management, 2005)
Occupational segregation by race and gender, though less common now than in the past, continues to be the norm rather than the exception in the sport industry. The purpose of this study was twofold. First, occupational segregation on the baseball playing field, often referred to as stacking, was discussed in light of human capital and social closure theories. Second, an attempt was made to replicate and extend a multivariate analysis of stacking by Margolis and Piliavin (1999) that challenges the dominant social science paradigm for explaining stacking. The present study uses more recent data than the Margolis and Piliavin study, as well as multinomial logistic regression analysis. The results reveal that stacking persists in Major League Baseball. They also reveal that the effect of race/ethnicity on assignments to playing positions is reduced when one controls for skills and physical characteristics such as speed and power hitting. The implications of this finding for sport management are examined.
Keywords: dept.psc

Impact of communication training on physician expression of empathy in patient encounters - Bonvicini, Kathleen A.; Perlin, Michael J.; Bylund, Carma L.; Carroll, Gregory; Rouse, Ruby A.; Goldstein, Michael G. (Patient Education and Counseling, 2009)
Objective: To examine whether an educational intervention that focused on physician communication training influenced physician ernpathic expression during patient interactions. Methods: This study used a quantitative research method to investigate the influence of communication training on physician-expressed empathy using two measures (global and hierarchical) of physician empathic behavior. Results: The differences in global empathy scores in the physician training group from baseline to follow-up improved by 37%, and hierarchical scores of physician empathic expression improved by up to 51% from baseline scores for the same group. Conclusions: The results strongly supported the hypotheses that training made a significant difference in physician empathic expression during patient interactions demonstrated by both outside observer measures of global ratings and hierarchical ratings of physician empathic behavior. Practice implications: These findings have significant implications for program design and development in medical education and professional training with the potential to improve patient outcomes. (C) 2008 Elsevier Ireland Ltd. All rights reserved.
Keywords: Adult; Communication; Education, Medical, Continuing; Educational intervention; Empathy; Female; Humans; Male; Measurement; Medical education; Middle Aged; Patient-Centered Care; Physician training; Physician-Patient Relations; Physician-patient relations; Quantitative; Research; United States; dept.pch

Pharmacist conscience clauses and access to oral contraceptives - Flynn, D. P. (Journal of Medical Ethics, 2008)
The introduction of conscience clauses after the 1973 US Supreme Court decision in Roe v. Wade allowed physicians and nurses to opt out of medical procedures, particularly abortions, to which they were morally opposed. In recent years pharmacists have requested the same consideration with regard to dispensing some medicines. This paper examines the pharmacists' role and their professional and moral obligations to patients in the light of recent refusals by pharmacists to dispense oral contraceptives. A review of John Rawls's concepts of the “original position” and the “veil of ignorance”, along with consideration of the concept of compartmentalisation, are used to assess pharmacists' requests and the moral and legal rights of patients to have their prescriptive needs met.
Keywords: *Continuity of Patient Care/st [Standards]; *Contraceptives, Oral/sd [Supply & Distribution]; *Moral Obligations; *Pharmaceutical Services/es [Ethics]; *Pharmacists/es [Ethics]; *Refusal to Treat/es [Ethics]; Continuity of Patient Care; Continuity of Patient Care/es [Ethics]; Contraceptives, Oral; Female; Humans; Moral Obligations; Pharmaceutical Services; Pharmaceutical Services/lj [Legislation & Jurisprudence]; Pharmacists; Refusal to Treat; Refusal to Treat/lj [Legislation & Jurisprudence]; Religion; dept.pch; ethics; female; human; legal aspect; morality; oral contraceptive agent; patient abandonment; patient care; pharmacist; pharmacy; religion; review; standard

Our men are grinding out: a qualitative examination of sex ratio imbalances, relationship power, and low-income African American women's health. - Bontempi, Jean M Breny; Eng, Eugenia; Quinn, Sandra Crouse (Women & Health, 2008)
In the United States, the number of HIV/AIDS cases among women of color is increasing, with African American women now comprising 60% of all female AIDS cases. Scholars have attributed this imbalance to social factors. The aim of this study was to explore the impact that relationship power has on heterosexual women's ability to practice safer sex. Five focus groups were conducted with 24 African American women, aged 18-57 years, residing in public housing in rural North Carolina over a six-month period in 2000. Findings suggest that women maintain their independence, despite inequities in relationship power and remain strong to make a better life for their families. Recommendations are made to promote and build upon this social identity that women have in order to help them practice healthier behaviors.
Keywords: *African Americans/px [Psychology]; *Cultural Characteristics; *Poverty/eh [Ethnology]; *Power, Psychological; *Sexual Behavior/eh [Ethnology]; *Women's Health/eh [Ethnology]; Adult; African American; African American women; African Americans; Anecdotes as Topic; Cultural Characteristics; Female; Focus Groups; HIV Infections; HIV Infections/eh [Ethnology]; HIV prevention; Health Knowledge, Attitudes, Practice; Human immunodeficiency virus infection; Humans; Middle Aged; North Carolina; Poverty; Power (Psychology); Qualitative research; Questionnaires; Safe Sex; Safe Sex/eh [Ethnology]; Sexual Behavior; Sexual Partners; Sexual Partners/px [Psychology]; Sexual health promotion; Surveys and Questionnaires; United States; Women's Health; adult; article; attitude to health; behavior; cultural factor; dept.pch; ethnology; female; human; information processing; literature; middle aged; poverty; psychological aspect; questionnaire; safe sex; sexual behavior; sexuality; women's health

Strategies for living long and healthy lives: Perspectives of older African/Caribbean-American women - Unson, Christine G.; Trella, Patricia M.; Chowdhury, Sutopa; Davis, Elizabeth M. (Journal of Applied Communication Research, 2008)
The influence of health and socioeconomic status on perceptions of aging and adaptation strategies of older African/Caribbean-American women was examined. Responses of 38 women (average age = 77.3 years) to: “What do you like and dislike about growing old?” and To what would you attribute your long life? were analyzed. Respondents were classified as: financially independent/healthy, financially dependent/healthy, financially independent/not healthy and financially dependent/not healthy. Narratives revealed declining health and restricted financial resources limited perceptions of opportunities for well-being. Despite differences in health and financial status, groups had some common strategies: avoiding risk behaviors, holding moral beliefs, optimism, altruism and spirituality. It was concluded that health and socioeconomic status had some influence on perceptions of aging and adaptation strategies.
Keywords: African-American; Aging perspectives; Caribbean-American; Older adult; dept.pch